Not All Clear Air Turbulence Is Kolmogorov—The Fine‐Scale Nature of Atmospheric Turbulence. Issue 2 (20th January 2023) - Rodriguez Imazio, Paola; Mininni, Pablo D.; Godoy, Alejandro; Rivaben, Nicolás; Dörnbrack, Andreas
Abstract: We study a strong clear air turbulence (CAT) event experienced by the German High‐Altitude Long‐Range research aircraft (HALO) during the Southern Hemisphere Transport, Dynamics, and Chemistry campaign. HALO encountered CAT leeward of the southern Andes Mountains, where tropospheric airflow favored vertically propagating mountain waves that were refracted southeastward into the core of tropopause jet. Turbulence is quantified using spectral quantities and structure functions computed from in situ 100 Hz flight level data. The detected CAT region exhibits strong patchiness, characterized by separated bursts in turbulent kinetic energy and energy dissipation rate. The high resolution in situ observations reveal different turbulent scaling within each patch, in both spectra and structure functions, and following Monin and Yaglom's conversion law. One patch follows power laws with exponents −1.71 ± 0.06, −1.771 ± 0.006, and −1.56 ± 0.05 for the velocity components w, v, and u, respectively, while another patch has exponents −2.17 ± 0.12, −2.50 ± 0.08, and −1.92 ± 0.09. These patches are mediated by a third patch with less clear scaling. While the patches can deviate from Kolmogorov scaling due to the anisotropy of the airflow, they still display evidence of CAT with enhanced energy dissipation rates. Plain Language Summary: Clear air turbulence (CAT) is a common phenomenon in upper layers of the atmosphere, often triggered by the instability of internal gravity waves or by strong wind shear. CAT can be disruptive for airplanes and uncomfortable for pilots and passengers. Nevertheless, the relationship between CAT formation and the resulting strength of bumpiness experienced by an aircraft is not fully understood. Most of these turbulent regions are patchy and exhibit sudden inhomogeneous bursts of velocity and temperature variations. However, CAT is often quantified using spectral quantities assuming isotropic and homogeneous turbulence. Here, we present a case study of a CAT event observed in the lowermost stratosphere during a research flight in the lee of the Andes Mountains near the Drake Passage in South America. The unique 100 Hz high resolution in situ observations allow the study of individual patches within the turbulent event. Their statistical properties can deviate significantly from those of homogeneous and isotropic turbulence, indicating thermal stratification as an important parameter determining the spectral response. Key Points: Moderate‐to‐severe clear air turbulence (CAT) over the Southern Andes is analyzed using 100 Hz in situ data obtained during a flight of the Southern Hemisphere Transport, Dynamics, and Chemistry campaign Vertical propagation of mountain waves in the lee of the Southern Andes is recognized as the main source for the turbulence observed Anisotropy due to thermal stratification results in turbulent patches within the CAT region with non‐Kolmogorov turbulence scaling